Incorporating double copies of a chromatin insulator into lentiviral vectors results in less viral integrants - Rosenqvist Nina; Jakobsson Johan; Nielsen Troels T; Lundberg Cecilia (BMC Biotechnology, 2009)
Abstract Background Lentiviral vectors hold great promise as gene transfer vectors in gene therapeutic settings. However, problems related to the risk of insertional mutagenesis, transgene silencing and positional effects have stalled the use of such vectors in the clinic. Chromatin insulators are boundary elements that can prevent enhancer-promoter interactions, if placed between these elements, and protect transgene cassettes from silencing and positional effects. It has been suggested that insulators can improve the safety and performance of lentiviral vectors. Therefore insulators have been incorporated into lentiviral vectors in order to enhance their safety profile and improve transgene expression. Commonly such insulator vectors are produced at lower titers than control vectors thus limiting their potential use. Results In this study we cloned in tandem copies of the chicken β-globin insulator (cHS4) on both sides of the transgene cassette in order to enhance the insulating effect. Our insulator vectors were produced at significantly lower titers compared to control vectors, and we show that this reduction in titer is due to a block during the transduction process that appears after reverse transcription but before integration of the viral DNA. This non-integrated viral DNA could be detected by PCR and, importantly, prevented efficient transduction of target cells. Conclusion These results have importance for the future use of insulator sequences in lentiviral vectors and might limit the use of insulators in vectors for in vivo use. Therefore, a careful analysis of the optimal design must be performed before insulators are included into clinical lentiviral vectors.